Analysis of the Effectiveness of the Cash Receipts Accounting System for Accounts Receivable (Case Study of PT. X) - Marwah, Mujahidah; Kurniati, Rini Rahayu; Anastuti, Karina Utami (CV. Proaksara Global Transeduka, 2024)
This research is descriptive qualitative, with the author's objective is to evaluate the efficiency of PT X's cash receipt accounting system in the cash receipt accounting system. Data collection methods include documentation, interviews, and observation. The Miles and Huberman model is used for technical analysis, and the triangulation method is used to ensure data validity. The results showed that the implementation of the accounting system function for cash receipts on receivables at PT Permata Delta Agung has implemented the accounting system function for cash receipts on receivables. However, the application has not been maximized because there are still accounting system functions that have not been carried out. The application of compliance with regulations at PT. X shows that there are still many pharmacies that do not comply with several policies that have been implemented by the company. for financial statement records in its implementation, PT. X has not yet made a general journal used. The procedure for receiving cash on accounts receivable, PT. X found that there was no application of the journal section function in preparing financial reports. This makes the cash receipt accounting system activities cannot be said to be running optimally. the internal control system implemented by PT. X is not optimal because the accounting function has not been implemented, there are no inspections carried out by internal control, there is no training to support employee development.